2007
DOI: 10.1126/science.1147635
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Carbon Nanotube Fiber

Abstract: With their impressive individual properties, carbon nanotubes should form high-performance fibers. We explored the roles of nanotube length and structure, fiber density, and nanotube orientation in achieving optimum mechanical properties. We found that carbon nanotube fiber, spun directly and continuously from gas phase as an aerogel, combines high strength and high stiffness (axial elastic modulus), with an energy to breakage (toughness) considerably greater than that of any commercial high-strength fiber. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
819
2
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 981 publications
(838 citation statements)
references
References 20 publications
13
819
2
4
Order By: Relevance
“…Their advantages for polymer reinforcement have been recently reviewed by Miyagawa et al and Coleman et al [29,30]. Koziol et al spun fibers from CNTs much stronger than in previous studies [31]. Such fibers can be imagined as a superior alternative to Kevlar.…”
Section: Introductionmentioning
confidence: 94%
“…Their advantages for polymer reinforcement have been recently reviewed by Miyagawa et al and Coleman et al [29,30]. Koziol et al spun fibers from CNTs much stronger than in previous studies [31]. Such fibers can be imagined as a superior alternative to Kevlar.…”
Section: Introductionmentioning
confidence: 94%
“…For example, prior to 2007, the reported tensile strengths of continuous CNT fibers without a coagulant lay in the range from 0.4 to 1.2 GPa, no matter if they were spun from a suspension. [5][6][7][8][9][10][11][12] Recently, Windle et al reported the synthesis of continuous high-performance CNT fibers with the highest strength value of 9 GPa. [12] This encouraging breakthrough enlightens the use of macroscale CNTs fibers as a structural reinforcement for many applications.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Recently, Windle et al reported the synthesis of continuous high-performance CNT fibers with the highest strength value of 9 GPa. [12] This encouraging breakthrough enlightens the use of macroscale CNTs fibers as a structural reinforcement for many applications. They pointed out that the obtained tensile strengths depended on the gauge lengths of the tested specimens: when the gauge length increased from 1 to 10 mm (a typical value for the tensile tests of CNT fibers), the average strength rapidly dropped to 1 GPa.…”
mentioning
confidence: 99%
“…Carbon nanotubes used in the study were synthesised via continuous CVD process [16]. Methane was used as the hydrocarbon feedstock and was injected into the hot furnace (1300°C) along with ferrocene and thiophene.…”
Section: Cnt Synthesis and Characterisationmentioning
confidence: 99%
“…In this paper, the presence of vertically aligned CNT arrays within epoxy matrix gives improved erosion resistance which opens up a new way for erosive wear applications of polymer composites using aligned CNTs. Inspired by this work, CNTs films synthesized by the continuous CVD process [16] can be assembled together to fabricate uni-or multi-directional CNT film/epoxy based composites. Such CNT structures can then be mechanically comparable to conventional fibre reinforced polymer composites.…”
Section: Introductionmentioning
confidence: 99%